2013
DOI: 10.1002/cncr.28220
|View full text |Cite
|
Sign up to set email alerts
|

Association of epidermal growth factor receptor mutations with human papillomavirus 16/18 E6 oncoprotein expression in non–small cell lung cancer

Abstract: BACKGROUND: Lung cancers in women, in nonsmokers, and in patients with adenocarcinoma from Asia have more prevalent mutations in the epidermal growth factor receptor (EGFR) gene than their counterparts. However, the etiology of EGFR mutations in this population remains unclear. The authors hypothesized that the human papillomavirus (HPV) type 16=18 (HPV16=18) E6 oncoprotein may contribute to EGFR mutations in Taiwanese patients with lung cancer. METHODS: One hundred fifty-one tumors from patients with lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
(68 reference statements)
1
23
0
Order By: Relevance
“…In a previous study that included squamous cell carcinomas, EGFR mutations were frequently observed in HPV-positive tumors (41 versus 20% in HPV-negative tumors, PZ0.006); however, the adjusted results did not remain significant (PZ0.111; Tung et al 2013). In another study including some non-classical EGFR-mutant tumors, old tuberculosis lesions were more frequently observed in EGFR-mutant tumors compared with wild-type tumors (80.6 versus 65.5%, PZ0.018).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In a previous study that included squamous cell carcinomas, EGFR mutations were frequently observed in HPV-positive tumors (41 versus 20% in HPV-negative tumors, PZ0.006); however, the adjusted results did not remain significant (PZ0.111; Tung et al 2013). In another study including some non-classical EGFR-mutant tumors, old tuberculosis lesions were more frequently observed in EGFR-mutant tumors compared with wild-type tumors (80.6 versus 65.5%, PZ0.018).…”
Section: Discussionmentioning
confidence: 74%
“…Several Asian investigators have suggested the contribution of infection, including human papillomavirus (HPV) and tuberculosis, to EGFR-mutant tumors , Tung et al 2013. In a previous study that included squamous cell carcinomas, EGFR mutations were frequently observed in HPV-positive tumors (41 versus 20% in HPV-negative tumors, PZ0.006); however, the adjusted results did not remain significant (PZ0.111; Tung et al 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ROS is a DNA-damaging agent that elevates the mutation rate and results in oncogenic transformation (Behrend et al 2003). The E6 oncoprotein causes oxidative stress in the cell leading to the DNA damage and giving rise to inactivation of the MMR pathway-responsible for controlling genetic stability by removing the bad base pairings-and thus increases the 8-OH-dG levels (Tung et al 2013). …”
Section: E6 and Egfr Mutationsmentioning
confidence: 99%
“…This leads to the accumulation of DNA damage and mutations that give rise to cell transformation and carcinoma development [9]. For example, the positive correlation of HPV 16/18 infection with the risk of epidermal growth factor receptor mutation occurrence has been shown in Taiwanese NSCLC patients [10]. Further insights into the mechanistic action of the E6 and E7 oncoproteins on tumor progression should be investigated.…”
Section: Introductionmentioning
confidence: 99%